A History of Lung Cancer - Timmermann, C. author. aut Link
X, 244 p.
Keywords: The first comprehensive history of lung cancer from around 1800 to the present day; a story of doctors and patients, hopes and fears, expectations and frustrations. Where most histories of medicine focus on progress, Timmermann asks what happens when medical progress does not seem to make much difference.